2007
DOI: 10.1243/09576509jpe372
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of different working fluids for use in organic Rankine cycles

Abstract: This article presents a second-law analysis for the use of organic Rankine cycle (ORC) to convert waste energy to power from low-grade heat sources. The organic working fluids were selected to investigate the effect of the fluid boiling point temperature on the performance of ORCs. The working fluids under investigation are R134a, R113, R245ca, R245fa, R123, isobutane, and propane, with boiling points between 243 and 48 °C. The results are compared with those of water under similar conditions. A combined first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 16 publications
1
58
0
6
Order By: Relevance
“…Mago et al [24] presented organic refrigerant need not be superheated as the thermal efficiency ratio remains constant when the inlet temperature of turbine is increased. Furthermore, superheating organic refrigerants increase the irreversibility in the second law analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mago et al [24] presented organic refrigerant need not be superheated as the thermal efficiency ratio remains constant when the inlet temperature of turbine is increased. Furthermore, superheating organic refrigerants increase the irreversibility in the second law analysis.…”
Section: Resultsmentioning
confidence: 99%
“…That is, ξ < 0: a wet fluid, ξ~0: an isentropic fluid, and ξ > 0: a dry fluid. Isentropic fluid R245fa was selected as the working fluid based on its good cycle performance [9,10] and eco-friendly characteristics [35], and it has been widely used in ORCs up to now and is researched quite well [36]. However, the global warming potential (GWP) of working fluid is not considered in this research.…”
Section: System Description and Assumptionsmentioning
confidence: 99%
“…Also, many investigations on ORC are mainly focused on the choices of the working fluid [7][8][9][10][11][12] and its performance [13][14][15][16][17][18][19][20][21]. Hung et al [13] discussed the irreversible loss of the key parts in ORC and found that the maximum irreversible loss happens in the evaporator.…”
Section: Introductionmentioning
confidence: 99%
“…Yet many challenges have to be faced before the vehicle integration. The first challenge deals with the correct choice of fluids and system architecture [Mago et al (2007), Grelet et al (2014)] and shows that system simulation is a critical part of the development work. The use of water-alcohol mixture can bring some advantages in the power recuperation and overcome both disadvantages of these fluids: high freezing temperature of water and flammability of alcohol [Latz et al (2012)].…”
Section: Introductionmentioning
confidence: 99%